Evidence of validity of internal structure of the Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being Scale (FACIT-Sp-12) in Brazilian adolescents with chronic health conditions - Alvarenga, Willyane de Andrade; Nascimento, Lucila Castanheira; Rebustini, Flávio; dos Santos, Claudia Benedita; Muehlan, Holger; Schmidt, Silke; Bullinger, Monika; Liberato, Fernanda Mayrink Gonçalves; Vieira, Margarida (Frontiers in Psychology, 2022)
This study explored the evidence of validity of internal structure of the 12-item Functional Assessment of Chronic Illness Therapy—Spiritual Wellbeing Scale (FACIT-Sp-12) in Brazilian adolescents with chronic health conditions. The study involved 301 Brazilian adolescents with cancer, type 1 diabetes mellitus, or cystic fibrosis. Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Item Response Theory (IRT) were used to test the internal structure. Reliability was determined with Cronbach’s Alpha and McDonald’s Omega. The EFA suggested a one-dimensional scale structure in contrast to the original 2-factor model or the 3-factor model which were not reproduced in the current CFA. All quality indicators for the EFA one-factor exceeded the required criteria (FDI = 0.97, EAP = 0.97, SR = 3.96 and EPTD = 0.96, latent GH = 0.90. and the observed GH = 0.85). The FACIT-Sp-12 for adolescents yielded strong evidence for a 1-factor model and with good reliability.